2022
DOI: 10.3389/fped.2022.875877
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-Phosphate Dehydrogenase Deficiency and Neonatal Hyperbilirubinemia: Insights on Pathophysiology, Diagnosis, and Gene Variants in Disease Heterogeneity

Abstract: Glucose-6-phosphate dehydrogenase (G6PD) deficiency is a prevalent condition worldwide and is caused by loss-of-function mutations in the G6PD gene. Individuals with deficiency are more susceptible to oxidative stress which leads to the classical, acute hemolytic anemia (favism). However, G6PD deficiency in newborn infants presents with an increased risk of hyperbilirubinemia, that may rapidly escalate to result in bilirubin induced neurologic dysfunction (BIND). Often with no overt signs of hemolysis, G6PD de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 96 publications
2
31
0
6
Order By: Relevance
“…So, to establish a certain diagnosis of G6PD insufficiency, genotyping of G6PD mutations is beneficial ( Jiang et al, 2006 ). In addition, the analysis of G6PD genotypes contributes to the study of molecular biology and genetic characterization of human populations ( Hamali, 2021 ; Lee et al, 2022 ). Aside from this, the genotyping of G6PD deficiency also has a significant impact on the field’s understanding of the disorder ( Li et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…So, to establish a certain diagnosis of G6PD insufficiency, genotyping of G6PD mutations is beneficial ( Jiang et al, 2006 ). In addition, the analysis of G6PD genotypes contributes to the study of molecular biology and genetic characterization of human populations ( Hamali, 2021 ; Lee et al, 2022 ). Aside from this, the genotyping of G6PD deficiency also has a significant impact on the field’s understanding of the disorder ( Li et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…G6PD, a key regulatory enzyme in the pentose phosphate pathway and an active cytosolic enzyme in red blood cells (RBCs), exists in various forms ( Luzzatto and Arese 2018 ). The mutation of G6PD gene can lead to the deficiency of activity, weaken the role in regulation of redox state, and cause a clinically common disease-G6PD ( Lee et al, 2022 ). Genetic analysis of G6PD-deficient patients indicated that different ethnic groups varied in their characteristic profiles of G6PD-deficiency variants ( Nkhoma et al, 2009 ).…”
Section: Discussionmentioning
confidence: 99%
“…16 Amongst the Middle East, Latin America, Africa, Asia, and the Mediterranean, the majority of G6PD enzyme deficiency lies in Asian countries due to high population density. 2,3 Besides, the global distribution of glucose-6-phosphate dehydrogenase deficiency is also related to the widespread occurrence of Plasmodium Falciparum malaria, as G6PD deficient patients may afford protection against malaria. 3,4 The incomplete expression, absence, or reduction of the enzyme leads to the deficiency of G6PD, which can be inherited or acquired.…”
Section: Introductionmentioning
confidence: 99%
“…2,3 Besides, the global distribution of glucose-6-phosphate dehydrogenase deficiency is also related to the widespread occurrence of Plasmodium Falciparum malaria, as G6PD deficient patients may afford protection against malaria. 3,4 The incomplete expression, absence, or reduction of the enzyme leads to the deficiency of G6PD, which can be inherited or acquired. The mutation in the G6PDX gene on the X-chromosome leads to the inherited X-linked recessive disorder, while ageing and conditions like metabolic syndrome can cause acquired deficiency.…”
Section: Introductionmentioning
confidence: 99%